Analysis and Improvement of Time Frames Management for Ischemic Stroke Services in the Emergency Room at Budi Medika Hospital, Bandar Lampung - Theng, Luther; Jak, Yanuar (Jurnal Health Sains, 2024)
Stroke is a catastrophic disease and a major health problem both in Indonesia and in the world. Stroke causes a high number of morbidities and mortalities. The philosophy of stroke"Time Is Brain", it requires good time frames management according to the world guidelines related to ischemic stroke services in emergency departments (ED). The design of the study is a quantitative descriptive with retrospective method within the period from January to December 2023, continued qualitatively a mix methodf explanatory sequential sequential. The number of samples is 150 which meets the inclusion criteria. Quantitative analysis with SPSS V29 for mac and quantitative with NVIVO 14. The Median of door to triage time at study point was 1(1-5) minutes, door to physician 2 (0-10) minutes, Door to CT scan 19.5 (2 -50) minutes, Door To CT interpretation wa 20.5 (2-200) minutes and Door To Drug was 63 (12-267) minutes. Logistics regression analysis of time frames showed that the most significant result was door to CT scan (OR:14.5,95%CI5.3-39.4,p<0.001). Moderated Regression Analysis (MRA) showed significant time frame influences p<0.001 and R2 96% with ischemic stroke service in IGD. To provide the good performance of Door to drug time£60 minutes requires good time frames management, role of five (5) M management (man, method, material, machine and money) and good stroke code implementation.